Յակոբ Դ. Ջուղայեցի կաթողիկոսը եւ հայ ազատագրական պայքարը 1655—1674 թթ. - Պօղոսեան, Տ. Արարատ Քհնյ. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Проходящая в первой половине XVII века «Тридцатилетняя война» (1618— 1648), а также Критская война (1645—1669) сформировали новую геополитическую ситуацию как на Западе, так и на Востоке. В этот период действия, инициированные народами, находящимися под властью Османской империи и Персии, были направлены на свержение ига указанных государств.“Thirty Years’ War” that took place in the first half of the 17th century (1618— 1648), as well as the Cretan War (1645—1669), created a new geopolitical situation in both the West and the East. During this period, the actions of the nations under the rule of both the Ottoman Empire and Persia were aimed at breaking the yoke of the rule of these states.“Thirty Years’ War” that took place in the first half of the 17th century (1618— 1648), as well as the Cretan War (1645—1669), created a new geopolitical situation in both the West and the East. During this period, the actions of the nations under the rule of both the Ottoman Empire and Persia were aimed at breaking the yoke of the rule of these states.
Keywords: History; Armenian church